NUMERAMENTALITY: THE STUDY OF PRACTICES AND GOVERNMENT IN MATHEMATICS (&) EDUCATION IN CONTEMPORANEITY. - Samuel Edmundo Lopez Bello (Editora da Universidade de Santa Cruz do Sul, 2012)
This paper aims to relate the notion of social practice, from the wittgensteinian perspective of language games as ruled activities, and the notion of governmentality of Michel Foucault, from which discusses the concept of "numeramentality" within what we consider to be a research program for discussing Mathematics Education in Contemporaneity. At the same time, it proposes a reflection on the analytical productivity of this concept in order to understand how a "numeramentalized" society by operating through discourses of truth and making use of numbers, ratios, measurements, practices produce different ways of being and acting of subjects by constituting individual and collective subjectivities in several socially institutionalized spaces.